Knowledge and Attitude toward Nursing Profession as a Career among Boy Students of Secondary Level School at Nawalpur District - Regmi, Kamala; Bhusal, Mina; Paudel, Madhu Maya; Dhakal, Bijaya (International Journal of Silkroad Institute of Research and Training, 2025)
Background: Nursing is a science and art that requires a blend of knowledge, skills, and values. It is an integral part of the healthcare system, and encompasses the promotion of health, prevention of illness, and care of disabled people of all ages. The study entitled "Knowledge and attitude toward nursing profession as a Career among boy students of secondary level school of Nawalpur district." The objectives of study were to assess the knowledge and attitude towards nursing profession as a career among boy students of secondary level. Method: A descriptive cross sectional study design was carried out among 224 boy students of secondary level of government school; Nepal Rastriya Smasher Aadarsha Secondary School Gaindakot-1 and Kalika Secondary school Gaindakot-8. Sample was selected using non-probability purposive sampling technique. Self-administered semi structured questionnaire was used to collect data. Obtained data was analyzed in SPSS version 20 by using descriptive and inferential statistics. Result: The finding of the study revealed that mean age was 15.05 (±1.078) years where most of the (67.9%) respondents were fall on 13 -15 years of age. Finding of the study showed that the level of knowledge toward nursing profession among boy students was 59.8% had average knowledge and 33.5% had adequate knowledge and 6.7% had inadequate knowledge. In relation to attitude 56.7% had positive attitude and 43.3% had negative attitude toward nursing profession. Conclusion: Based on the finding of the study, it was concluded that there was inadequate knowledge and less positive attitude towards the nursing profession. Hence, Educational programs regarding different aspects of nursing profession should be planned timely by professional nursing organizations, nursing colleges and secondary schools of Nepal which would create a positive impact in male nursing students in coming academic years.